Nutritional and Functional Properties of Wild Leafy Vegetables for Improving Food Security in Southern Angola - Kissanga, Raquel (2022)
In Southern Angola, numerous non-woody forest products are sold at local markets, namely in Lubango (Huíla Province). Such is the case of herbaceous wild plants, locally known as lombi, which are sold fresh throughout the year and cooked as a vegetable. Although these wild leafy vegetables are commercialized and widely used in local food, there is still a lack of scientific knowledge about their properties. Thus, this study aimed to identify and characterize the species sold, and to determine their nutritional and functional properties. Our results revealed that three species—Amaranthus hybridus, Bidens pilosa, and Galinsoga parviflora—are usually sold at Lubango markets and consumed by local populations. These are annual exotic plants, native to Southern America, and usually occur spontaneously in croplands or disturbed areas, but can also be cultivated, particularly A. hybridus. Physico-chemical analyses of lombi species and mixtures sold at the markets included measurements of moisture, protein, lipid, and mineral content, as well as total phenolic content, antioxidant activity, and levels of heavy metal contaminants. The results revealed that lombi contain a significant amount of protein (20–28 g/100 g, dry basis), high values of macronutrients and micronutrients, as well as of phenolic compounds (10–40 mg GAE/g) and a good antioxidant capacity. Given the availability of lombi throughout the year, our study demonstrated the importance of wild edible plants in Angola, both as a valuable natural resources and as a complementary food sources, as well as additional sources of income for many families.